IJCM_285A: Tuberculosis Preventive Treatment among the Household Contacts of Tuberculosis Patients - Coverage and Correlates in a Block of Murshidabad District, West Bengal: A Cross-sectional Study - Mukherjee Ophelia; Das Dilip Kumar; Adhikary Mrinmoy; Ghosh Ritu (Wolters Kluwer Medknow Publications, 2024)
Background: Tuberculosis preventive treatment (TPT) among close contacts of Tuberculosis (TB) cases is a globally accepted strategy. India targeted elimination of TB by 2025 and started implementing TPT among all household contacts. This intervention needs evaluation in different areas and population groups for effective outcome. Objectives: We aimed to assess the extent of TPT coverage and adherence; ascertain the reasons for non-initiation and non-adherence; and to determine the socio-demographic and programmatic correlates of coverage. Methodology: We conducted a descriptive cross-sectional study during September-November 2023 in a block of Murshidabad district, West Bengal. A sample of 301 eligible household contacts (HHC) of 'index cases' (microbiologically-confirmed drug-sensitive pulmonary TB) registered in TB unit of the block during October'22 to March'23 were the study subjects. For child contacts (<12 years), mothers were considered respondents. Participants/respondents were interviewed with a pre-designed schedule with prior informed consent. Descriptive and inferential statistics were applied for analysis through Statistical Package for Social Sciences (version 20). Results: Of 301 contacts, 179 (59.5%) individually traced/counseled at the household; 238 (79.1%) were screened for TB symptoms; 28(11.3%) had sputum examination. TPT initiation rate was 74.8% (225/301) with 47.1% within seven days of diagnosis of index case; not offered by health care providers (59.2%) being major reason for non-initiation. Completion rate with adherence to full course was 69.3% (156/225); perceived lack of need (50.7%), migration (21.7%) being major reasons for non-adherence. Overall coverage of full course TPT among total eligible contacts was only 51.8% (156/301). On multivariable logistic regression; male gender (AOR=1.982; 95% CI=1.004-3.915), HHC with individual tracing/counseling (AOR=13.507; 95% CI= 6.781-26.906) and who had symptoms screening (AOR=5.694; 95% CI=2.223-14.587) predicted significantly higher TPT coverage. Conclusion: Cascade of care indicators for TPT remains suboptimal in the area and highlights the need for further strengthening of programmatic aspects of its implementation.